2021
DOI: 10.1186/s43141-021-00269-1
|View full text |Cite
|
Sign up to set email alerts
|

Picloram-induced enhanced callus-mediated regeneration, acclimatization, and genetic clonality assessment of gerbera

Abstract: Background Gerbera jamesonii Bolus ex Hooker f. (African daisy) is listed among the top five most important ornamental plants in the global floricultural industry. To satisfy its demand, the floriculture industry relies on reproducible and effective propagation protocol while retaining the genetic uniformity of G. jamesonii. The present study, for the first time, reports the potential of picloram for enhanced induction of organogenic calli from leaves of G. jamesonii and its high-frequency indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…For instance, Kashanchi et al 15 reported callus induction of P. alkekengi in 1/2 MS medium supplied with 2, 4-D (2 mgL −1 ), and organogenesis was observed during callus growth. Picloram at 1 mgL −1 concentration increased markedly days to callus induction and callus diameter in gerbera 21 and also, in combination with BAP (5 mgL −1 ), induced maximum callus formation in Simmondsia chinensis 22 , which may be associated with its impact on cell elongation and division through the responsive gene expressions 23 . However, in Eupatorium adenophorum , picloram stimulated electrolyte leakage and malondialdehyde productions and decreased callus biomass at high concentrations 24 .…”
Section: Discussionmentioning
confidence: 91%
“…For instance, Kashanchi et al 15 reported callus induction of P. alkekengi in 1/2 MS medium supplied with 2, 4-D (2 mgL −1 ), and organogenesis was observed during callus growth. Picloram at 1 mgL −1 concentration increased markedly days to callus induction and callus diameter in gerbera 21 and also, in combination with BAP (5 mgL −1 ), induced maximum callus formation in Simmondsia chinensis 22 , which may be associated with its impact on cell elongation and division through the responsive gene expressions 23 . However, in Eupatorium adenophorum , picloram stimulated electrolyte leakage and malondialdehyde productions and decreased callus biomass at high concentrations 24 .…”
Section: Discussionmentioning
confidence: 91%
“…However, limited study had been carried out on callus induction in C. nutans (Bong et al, 2021;Hashim et al, 2021 andPhua et al, 2016) [24,[33][34] whereby callus study was carried out using limited plant growth regulators (2,4-D,Kinetin and BAP). To date, no callus study had been initiated using Picloram in C. nutans though many callus induction studies using Picloram had been reported in other medicinal plants (Gnasekaran et [35][36][37][38] . This is first study in C. nutans to induce callus using Picloram as one of the plant growth regulators.…”
Section: Introductionmentioning
confidence: 99%